Comparing fiber quality characteristics and staple length in Suri and Huacaya alpacas - Pinares, Rubén; Meza, Aydee; Crispín, Neyla; Lozano, Franklin; Pezo, Danilo (Frontiers in Animal Science, 2023)
The textile industry considers alpaca fiber to be a specialty fiber. The aim of this study was to evaluate the influence of color, fiber type, location, age and sex of alpacas on fiber quality characteristics and staple length. Fiber samples were taken from mid side of 118 Huacaya and Suri alpacas in two livestock shows (Pitumarca and Maranganí) and CICAS La Raya (South American Camelid Research Center) located at province of Canchis (Cusco, Peru). The fiber textile characteristics and staple length in black alpaca is similar to brown alpaca. Huacaya fiber is finer, having lower MFD, SD and coefficient of variation of MFD compared to Suri fiber. Alpacas from two livestock shows have higher quality fiber compared to no selected alpacas raised in CICAS La Raya. Staple length is longer in Suri alpaca compared to Huacaya. Likewise, the staple length is higher in alpacas from Pitumarca, followed by alpacas from Maranganí and is lower in alpacas from CICAS La Raya. Young alpacas have shorter staple length than adults, and it is longer in females than males. The mean fiber diameter and spinning fineness are strongly correlated with other fiber characteristics in colored alpacas. Furthermore, black and brown alpacas raised in small herds, judged in two livestock shows produce fiber at 22 µm for the textile industry.